Microbial Pattern of Infection of a Post PTB Patient in Cumilla Region (The Planet, 2024)
Introduction: Pulmonary tuberculosis (PTB) remains a significant public health challenge in Bangladesh. Post-treatment complications and the emergence of antimicrobial resistance complicate patient management. This study aims to investigate the microbial infection patterns, demographic characteristics, and antimicrobial resistance in post-PTB patients in Cumilla, Bangladesh. Methods & Materials: This observational study was conducted from January 2022 to December 2023 at Mynamati Cantonment General Hospital, Cumilla. A total of 83 post-PTB patients aged 20 years and above participated. Data on demographics, clinical characteristics, and comorbidities were collected using a pre-structured questionnaire. Standard Culture and Sensitivity (C&S) tests were performed to determine antimicrobial sensitivity and resistance patterns. Data were analyzed using SPSS version 25. Results: The majority of participants were aged 51-70 years (60.25%) and predominantly male (66.27%). Common occupations included farming (40.96%) and private jobs (31.33%). Family income was mostly between 5000 and 10000 BDT per month (51.81%). Comorbid conditions included COPD (36.14%), diabetes (25.30%), and hypertension (20.48%). Biochemical parameters showed mean WBC count of 11036.34±4770.48, platelet count of 196528.00±72250.40, and ESR of 31.42±12.15. Antimicrobial sensitivity was highest for levofloxacin (33.73%) and ciprofloxacin (26.51%). High resistance was noted for cefixime (48.19%), cefuroxime (46.99%), and azithromycin (42.17%). Conclusion: The study highlights significant comorbidities and high antimicrobial resistance in post-PTB patients, emphasizing the need for integrated care approaches and continuous surveillance of antimicrobial susceptibility. Tailoring treatment protocols based on local epidemiological data is crucial for improving patient outcomes and managing multidrug-resistant TB effectively.
Keywords: Pulmonary Tuberculosis; Antimicrobial Sensitivity; Antimicrobial Resistance